The diagnostic utility of urinary Transferrin excretion rate as predictor for micro albuminuria in patients with Type 2 Diabetes Mellitus among Karbala province - Almaialy, Zahraa Abduladheem; Baidah, Rabab Salman; Al-Issawi, Hosam A.A.; Hussein, Muna Ali (Technium BioChemMed, 2024)
One of the factors responsible of end-stage renal disease and chronic kidney disease is diabetic nephropathy. Microalbuminuria itself is regarded as the initial indication of diabetic nephropathy, and it affects 20% to 40% of patients with diabetes mellitus. Because of the limited accuracy and precision of microalbuminuria, more susceptible markers may be developed to more accurately identify diabetic nephropathy early on. The purpose of this research was to ascertain whether urine transferrin could be used as a marker for diabetic nephropathy. In our research, 80 subjects with type 2 diabetes were divided into two categories: 10 healthy controls and group 1 (normoalbuminuric, with albumin excretion up to 30 mg/d) and group 2 (microalbuminuric, with albumin excretion between 30 and 300 mg/d). all subjects was over the age of 18, had diabetes for further than a year, and had a glomerular filtration rate greater than 60 mL/min/1.73 m2. The concentration of transferrin, serum creatinine, and glycosylated hemoglobin (HbA1c) in both spot urine and 24-hour urine samples were assessed using a super accurate sandwich enzyme - linked immunosorbent assay kit. subjects with microalbuminuria had substantially greater urinary transferrin levels than both normoalbuminuric and healthy control participants. We discovered a significantly positive correlation r = 0.584 (p < 0.001) when we compared these categories based on the urinary transferrin concentration. Urinary transferrin levels did not correlate with glycoregulation, and neither did transferrin levels and the length of diabetes. Urinary transferrin levels may be utilized as an important indicator of diabetic nephropathy, according to the findings of the research.